Belediyelerin İlan ve Reklam Vergisi Uygulamaları Üzerine Bir Değerlendirme - Duru, Ahmet Alptekin (Muş Alparslan Üniversitesi, 2020)
Announcement and Advertisement Tax is a municipal revenue but also it has an extra-fiscal purpose which is decreasing the density of signboards in the city. There has been not a separate article in the literature analyzing the dual functions, the subject, the coverage and tariff, the share in the municipal revenue, the division of collection authority between the district municipality and the metropolitan municipality in the metropolitan area of the Announcement and Advertisement Tax. These issues are analyzed via review of the regulations, court orders and budget realizations of the municipalities. Therefore, the problems arising in practice are determined. Consequently, several suggestions developed such as tariffs and taxable events should be updated, municipalities should have the power to determine the tariff, and the district municipality should be the collection authority in the metropolitan area.

İlan ve Reklam Vergisi’nin bir belediye geliri olmanın yanı sıra kentte tabela yoğunluğunu azaltmak gibi mali olmayan bir amacı da vardır. İlan ve Reklam Vergisi’nin bu iki işlevini, konusunu, kapsamını ve tarifesini, belediye gelirleri içindeki yerini, tahsil etme yetkisi açısından büyükşehir belediyeleri ve büyükşehir ilçe belediyeleri arasındaki durumunu inceleyen müstakil bir çalışmaya literatürde rastlanmamıştır. Sayılan bu hususlar mevzuat taraması, mahkeme kararları ve belediyelerin bütçe gerçekleşme sayıları üzerinden bu makalede incelenerek uygulamada karşılaşılan sorunlar tespit edilmeye çalışılmıştır. Sonuç olarak makalede kanundaki tarifelerin ve vergiyi doğuran olayların güncellenmesi, belediyelere tarife belirleme yetkisi verilmesi ve büyükşehirlerde bu vergiyi toplama yetkisinin tamamen ilçe belediyelerine bırakılması önerilmektedir.
An Evaluation of the Announcement and Advertisement Tax Practices of the Municipalities
anemon
Keywords: Announcement and Advertisement Tax; Signboard; Tax tariff; Municipality; Metropolitan municipality; İlan ve Reklam Vergisi; Tabela; Vergi Tarifesi; Belediye; Büyükşehir Belediyesi